Fuzzy Modeling and Impulsive Control of a Memristor-Based Chaotic System - 钟其水 于永斌 虞厥邦 (Chinese physics letters, 2010)
We mainly investigate the issues of fuzzy modeling and impulsive control of a memristor-based chaotic system and present a memristor-based chaotic system as the Takagi-Sugeno model-based fuzzy system. Then, based on the impulsive control theory of dynamical systems, a criterion ensuring impulsive stabilization of the memristorbased chaotic system is derived for the first time. An illustrative example is given to verify the effectiveness of the control scheme.